A New Role for SMCHD1 in Life's Master Switch and Beyond. Issue 12 (December 2019) - Schall, Peter Z.; Ruebel, Meghan L.; Latham, Keith E.
Abstract : Structural maintenance of chromosomes flexible hinge-domain containing protein 1 (SMCHD1) has emerged as a key regulator of embryonic genome function. Its functions have now extended well beyond the initial findings of effects on X chromosome inactivation associated with lethality in female embryos homozygous for a null allele. Autosomal dominant effects impact stem cell properties as well as postnatal health. Recent studies have revealed that SMCHD1 plays an important role as a maternal effect gene that regulates the master switch of life, namely embryonic genome activation, as well as subsequent preimplantation development and term viability. These discoveries mark SMCHD1 as a major regulator linking developmental processes to adult disorders including a form of muscular dystrophy. Highlights: The first burst of mouse embryonic genome activation (EGA1) is short-lived, and must be initiated and terminated in a timely manner for maximum embryo viability. A new pathway has recently emerged that controls the onset and termination of EGA1 by the transcriptional activator, developmental pluripotency associated gene 2 (DPPA2), and by the transcriptional repressor, SMCHD1. Following EGA1, a transcriptionally repressive state is established to allow thousands of other genes to be regulated correctly. Oocyte- and embryo-expressed SMCHD1 is poised to play a significant role in establishing this repressive chromatin state. In humans, mutations in SMCHD1 contribute to facioscapulohumeral muscular dystrophy and Bosma arhinia microphthalmia syndrome. These effects suggest that at least part of this regulatory pathway functions during later development.